(untitled) (Research, Society and Development, 2026)
Ischemic heart disease remains a major cause of morbidity and mortality and results from reduced coronary blood flow. Coronary artery bypass grafting (CABG) is indicated in advanced cases; however, it is associated with respiratory and functional impairments in the postoperative period. Frailty, defined as reduced physiological reserve and functional capacity, negatively affects surgical outcomes regardless of age, making its preoperative assessment clinically relevant. Objective: To evaluate frailty, respiratory muscle strength, and functionality in patients undergoing CABG in the preoperative and postoperative periods. Materials and Methods: This cross-sectional, observational, and quantitative study included patients aged ≥42 years undergoing elective CABG at a university hospital in western Paraná, Brazil. Preoperative and postoperative assessments included the Edmonton Frail Scale, the Timed Up and Go (TUG) test, handgrip strength dynamometry, and manovacuometry to measure maximal inspiratory pressure (MIP) and maximal expiratory pressure (MEP). Results: A statistically significant reduction in right-hand (p=0.019) and left-hand (p=0.011) grip strength was observed postoperatively. Manovacuometry demonstrated a significant decrease in MEP (p=0.007), whereas no significant difference was found in MIP (p=0.101). Functional performance worsened in the postoperative period, evidenced by a significant increase in TUG completion time (p=0.037). The mean Edmonton Frail Scale score was 5.82 points, with most participants classified as vulnerable or frail. Conclusion: The findings demonstrate postoperative respiratory and functional impairment in patients undergoing CABG and highlight the importance of preoperative frailty assessment and the implementation of physiotherapeutic prehabilitation strategies to optimize recovery and preserve functional capacity.